2021
DOI: 10.1080/21655979.2021.1890399
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Prognostic Risk Factors of Synaptojanin 2 and Its Underlying Perturbations Pathways in Hepatocellular Carcinoma

Abstract: Synaptojanin 2 (SYNJ2) regulates cell proliferation and apoptosis via dephosphorylating plasma membrane phosphoinositides. Aim of this study is to first seek the full-scale expression levels and potential emerging roles of SYNJ2 in hepatocellular carcinoma (HCC). We systematically analyzed SYNJ2 mRNA expression and protein levels in HCC tissues based on large-scale data and in-house immunohistochemistry (IHC). The clinical significance and risk factors for SYNJ2-related HCC cases were identified. A nomogram of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 53 publications
(59 reference statements)
0
7
0
Order By: Relevance
“…Distinct SYNJ2 expression levels were identified in 14 types of cancer cell lines. Previous research showed differential expression levels of SYNJ2 between some cancers (e.g., BRCA [ 14 ] and LIHC [ 32 ]) and their control samples, and our study further comprehensively analyzed 20 cancers and revealed that increased and decreased SYNJ2 expression levels were defined in seven cancers (CHOL, COAD, LIHC, LUAD, LUSC, PRAD, and STAD) and four cancers (GBM, KICH, KIRC, and KIRP), respectively. SYNJ2 expression made it feasible to differentiate multiple types of cancers from their corresponding normal samples with at least moderate accuracy, suggesting its potential in identifying cancer status.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Distinct SYNJ2 expression levels were identified in 14 types of cancer cell lines. Previous research showed differential expression levels of SYNJ2 between some cancers (e.g., BRCA [ 14 ] and LIHC [ 32 ]) and their control samples, and our study further comprehensively analyzed 20 cancers and revealed that increased and decreased SYNJ2 expression levels were defined in seven cancers (CHOL, COAD, LIHC, LUAD, LUSC, PRAD, and STAD) and four cancers (GBM, KICH, KIRC, and KIRP), respectively. SYNJ2 expression made it feasible to differentiate multiple types of cancers from their corresponding normal samples with at least moderate accuracy, suggesting its potential in identifying cancer status.…”
Section: Discussionmentioning
confidence: 53%
“…Previous studies have reported that SYNJ2 is responsible for tumor initiation and progression. With genetic changes, SYNJ2 triggers colorectal cancer [ 10 ], medulloblastoma [ 9 ], prostate cancer [ 11 ], and hepatocellular carcinoma [ 32 ]. Overexpressed SYNJ2 boosts the invasion and migration of glioma [ 13 ] and breast cancer cells and prompts poor prognosis for cancer patients [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results were consistent with a recent study in which a high mutation rate of INPP5B was observed in the genome-wide mapping of melanocytic neoplasms [ 25 ]. Furthermore, changes in the expression of INPP5B have also been found in the metabolomic data of hepatocellular carcinoma [ 26 ]. These findings suggested that loss of function or lower functioning of INPP5B might be related to the initiation and progression of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, studies had reported that POLR2A gene polymorphism was associated with lower survival outcomes in patients with non-small cell lung cancer ( Sainsbury et al, 2015 ). In addition, Zhang et al discovered the key potential transcription axis of CTCF/POLR2A—SYNJ2/INPP5B in metabolic programs based on the ChIP-seq data set, speculated that CTCF/POLR2A could directly dysregulate SYNJ2 levels and that increased SYNJ2 would affect HCC development via metabolic perturbation pathways ( Zhang et al, 2021 ). The above studies consistently show that POLR2A promotes tumor growth and is related to poor prognosis.…”
Section: Discussionmentioning
confidence: 99%